Pendampingan Penyusunan Laporan Sistem Akuntansi Penerimaan Kas Pada Toko Bangunan Kembar Jaya di Kabupaten Sorong - Pasaribu, Sandi H.; Marani, Marsya (Yayasan Daarul Huda Kruengmane, 2023)
Community Empowerment is a development process in which the community takes the initiative to start a social activity process to improve their own situation and condition. Community empowerment will be successful or can occur if residents participate. Community empowerment also has several principles in its implementation, namely raising awareness of the community, providing education and training, organizing, developing strength, and developing dynamics (decisions in the hands of the community itself).